Uncertainty during pain anticipation: The adaptive value of preparatory processes. Issue 2 (16th October 2014) - Seidel, Eva‐Maria; Pfabigan, Daniela M.; Hahn, Andreas; Sladky, Ronald; Grahl, Arvina; Paul, Katharina; Kraus, Christoph; Küblböck, Martin; Kranz, Georg S.; Hummer, Allan; Lanzenberger, Rupert; Windischberger, Christian; et al.
Abstract Objectives: Anticipatory processes prepare the organism for upcoming experiences. The aim of this study was to investigate neural responses related to anticipation and processing of painful stimuli occurring with different levels of uncertainty. Experimental design: Twenty‐five participants (13 females) took part in an electroencephalography and functional magnetic resonance imaging (fMRI) experiment at separate times. A visual cue announced the occurrence of an electrical painful or nonpainful stimulus, delivered with certainty or uncertainty (50% chance), at some point during the following 15 s. Principal observations: During the first 2 s of the anticipation phase, a strong effect of uncertainty was reflected in a pronounced frontal stimulus‐preceding negativity (SPN) and increased fMRI activation in higher visual processing areas. In the last 2 s before stimulus delivery, we observed stimulus‐specific preparatory processes indicated by a centroparietal SPN and posterior insula activation that was most pronounced for the certain pain condition. Uncertain anticipation was associated with attentional control processes. During stimulation, the results revealed that unexpected painful stimuli produced the strongest activation in the affective pain processing network and a more pronounced offset‐P2. Conclusions: Our results reflect that during early anticipation uncertainty is strongly associated with affective mechanisms and seems to be a more salient event compared to certain anticipation. During the last 2 s before stimulation, attentional control mechanisms are initiated related to the increased salience of uncertainty. Furthermore, stimulus‐specific preparatory mechanisms during certain anticipation also shaped the response to stimulation, underlining the adaptive value of stimulus‐targeted preparatory activity which is less likely when facing an uncertain event. Hum Brain Mapp 36:744–755, 2015. © 2014 Wiley Periodicals, Inc.